Peranan Room Boy Dalam Menjaga Kebersihan Hotel Guna Menciptakan Kepuasan Tamu Hotel (Studi Kasus Pada Hotel Bumi Wiyata Depok Jawa Barat) - Kairudin Suwardi; Wisnu Hadi - AKPAR BSI Yogyakarta (Universitas Bina Sarana Informatika, 2012)
The existence of a room boy in a hotel activity has a role and meaning of itself. One of the most important parts that had by the hotel concerns with the maintenance of cleaning hotel, so that there is a part of housekeeping department in each hotel. This is the department which is responsible for the hotel’s comfortability. Room boy is a part of housekeeping department that has a duty and responsibilty to keep and improve the hotel’s cleaning and comfortability, especially for hotel room. The objective of this research is to know how far the room boy’s effort to keep and improve the cleaning of hotel room in order to create the satisfaction of guest hotel. The research is conducted by observation, interview, documentation, and review literature. The result of the research shows that room boy has conducted a duty and responsibility depends on the prosedure that is admitted by hotel management; which is conducting Step by Step Cleaning Procedure depends on the admission of hotel management, conducting morning briefing before room boy start to work, recheck the cleaning and room equipments depends on standard of hotel management, conducting daily programs, conducting general cleaning, conducting study banding and training both in-house training and out-house training. Key Word: Room Boy, Hotel Higinies, Guest Satisfaction